The Physicochemical Properties of the Biochar from Oil Palm Residues in ASEAN - Joni Jupesta; Keigo Akimoto; Edi Iswanto Wiloso; Shabbir Gheewala (Indonesian Journal of Life Cycle Assessment and Sustainability)
The forthcoming IPCC 6th Assessment Report has mentioned that the nature-based solutions for carbon dioxide removal are less costly, closer to deployment, and more vulnerable to reversal, compared to technology-based ones. Biochar, produced from biomass through pyrolysis process, is one such nature-based solution that can help reducing greenhouse gas emissions via soil carbon sequestration. Oil palm biomass residues, namely, empty fruit bunches, mesocarp fiber, oil palm frond, oil palm trunk, and palm kernel shell, are abundant in ASEAN countries, especially in Indonesia, Malaysia, and Thailand. These residues can be used to produce biochar through thermochemical conversion, so called pyrolysis. This study aims to provide a literature review on the physicochemical properties of biochar production from the palm oil residues mentioned above in the Southeast Asia region. There are ten parameters reviewed such as yield, physical properties (i.e., moisture content, volatile content, fixed carbon content, and energetic value), as well as chemical properties (i.e., C, H, O, N, and ash content) under different temperatures for all palm oil residues. Future research is field application of biochar for soil carbon sequestration and life cycle assessment of biochar production and field application. It is expected that the study could give information to relevant stakeholders on the potential of biochar from oil palm residues in ASEAN as one of nature-based solutions to reduce GHG emissions.